Desafio Baja - Riedel, Fernando Vendramini [UNESP]; Menossi, Leonardo Olbrick Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The main purpose of this presentation is show the essence of our extension project called “Desafio Baja”, as well as explaining the activities carried out with the community around the university. Furthermore, some inserted pictures may reflect not only the participation and organization of events, but also some awards won recently by our team.

O presente trabalho motiva-se a introduzir a essência do projeto de extensão “Desafio Baja”, bem como explanar as atividades vinculadas a equipe com a comunidade, por meio de imagens dos eventos realizados e que contém participação e títulos conquistados pela equipe TEC Ilha Baja.
Keywords: Events; Community; Baja; Baja; Comunidade; Eventos